MANAGEMENT AND LEADERSHIP'S IMPACT ON PERFORMANCE AT THE LEVEL OF THE ROMANIAN SCHOOL ORGANIZATION - Petruta Ionela STANCA; Tudor TARBUJARU (Management & Marketing)
The form of management practiced in most schools in Romania is the bureaucratic model. It is based on hierarchical authority, division of labor (teachers teaching different subjects), rules and regulations for students and subordinates, strict control by superiors/teachers, impersonal relationships between teachers and students, between managers and teachers, limitation of personal initiative in solving problems. In this situation, the educational goals of the school risk being subordinated to centralizing formalities and procedures. A basic condition of leadership, influence means respect, knowledge, cooperation and open communication at the level of the organization, combined efforts through motivation, enthusiasm and transformation in the direction of achieving performance. Ideally, all managers should also be leaders, but this happens, unfortunately, quite rarely. Educational leadership activates a set of behavioral rules and values that, through certain relationships, determine the evolution of attitudes and behaviors, as well as the quality of the results obtained. In order to reduce the negative consequences of this way of organization, specialists recommend combining management with leadership and adapting them to the particular situations of the school, so that creativity and personal initiative can be encouraged, the key factors of progress. The variety of leadership models based on interest in people demonstrates that there is no perfect leadership, but a combination of types of influence that highlights the need for managers to simultaneously manifest themselves as leaders of the people they lead. The article undertaken is intended to pertinent and coherent analysis of management and leadership, of the basic concepts that define them, through the prism of reporting to the need to improve performance at the level of the school organization. The goal of the study is to determine how management and leadership influence organizational performance.